(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
The article is devoted to a linguistic and translational analysis of the semantic adaptation of information technology (IT) terms that have entered the Uzbek language from English. The study studies the problems of the assimilation of IT terms in the Uzbek language, translation methods, lexical-semantic properties, and their consistent and correct use.